JURIDICAL OVERVIEW OF CARBON TRADING PROCEDURES VIA CARBON EXCHANGE - Karim, Abdul (JURNAL RISET INDRAGIRI, 2024)
The carbon trading mechanism is one of three ways to reduce emissions stipulated by the United Nations (UN) climate agreement, the Kyoto Protocol, on 11 December 1997. This world agreement was ratified by Indonesia into Law Number 17 of 2004 concerning Ratification of the Kyoto Protocol To The United Nations Framework Convention On Climate Change (Kyoto Protocol to the United Nations Framework Convention on Climate Change). This international agreement continues with the Paris Agreement To The United Nations Framework Convention On Climate Change (Paris Agreement to the United Nations Framework Convention on Climate Change) which has also been ratified by Indonesia with Law Number 16 of 2016. However, it is a shame that the carbon trading mechanism is not widely known to many actors, so the volume of carbon trading has not yet grown. One of the reasons is the lack of literacy in the carbon trading system. This research is doctrinal research with the aim of uncovering facts regarding the mechanism and trading system of Carbon Trading through the Carbon Exchange in order to provide a comprehensive understanding to the public. The results of the research show that the Carbon Trading mechanism through the Carbon Exchange in Indonesia has been implemented but is still relatively new. There are several regulations issued by several different institutions. The intensity of Carbon Trading activities through the Carbon Exchange shows that conditions are only in the introduction stage, and have not yet grown significantly. The author recommends that carbon trading socialization activities be carried out in a structured, systematic and massive manner so that people quickly understand and can ultimately take advantage of the economic opportunities contained in carbon trading